Recasting German identity culture, politics, and literature in the Berlin Republic - Taberner, Stuart; Finlay, Frank (Boydell & Brewer, 2002)
This collection of fifteen essays by scholars from the UK, the US, Germany, and Scandinavia revisits the question of German identity. Unlike previous books on this topic, however, the focus is not exclusively on national identity in the aftermath of Hitler. Instead, the concentration is upon the plurality of ethnic, sexual, political, geographical, and cultural identities in modern Germany, and on their often fragmentary nature as the country struggles with the challenges of unification and international developments such as globalization, multiculturalism, and postmodernism. The multifaceted nature of German identity demands a variety of approaches: thus the essays are interdisciplinary, drawing upon historical, sociological, and literary sources. They are organized with reference to three distinct sections: Berlin, Political Formations, and Difference; yet at the same time they illuminate one another across the volume, offering a nuanced understanding of the complex question of identity in today's Germany. Topics include the new self-understanding of the Berlin Republic, Berlin as a public showcase, the Berlin architecture debate, the Walser-Bubis debate, fictions of German history and the end of the GDR, the impact of the German student movement on the FRG, Prime Minister Biedenkopf and the myth of Saxon identity, women in post-1989 Germany, trains as symbols and the function of the foreign in post-1989 fiction, identity construction among Turks in Germany and Turkish self-representation in post-1989 fiction, the state of German literature today. Contributors: Frank Brunssen, Ulrike Zitzlsperger Janet Stewart, Kathrin Schödel, Karen Leeder, Ingo Cornils, Peter Thompson, Chris Szejnmann, Sabine Lang, Simon Ward, Roswitha Skare, Eva Kolinsky, Margaret Littler, Katharina Gerstenberger, and Stuart Parkes. Stuart Taberner is Lecturer in German, and Frank Finlay is Professor of German and Head of the Department of German, both at the University of Leeds, UK.
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Geschichte 1900-2000; Geschichte 1989-2002; Psychologie; National characteristics, German; Holocaust, Jewish (1939-1945) / Psychological aspects; German literature / 20th century / History and criticism; Literatur; Kulturelle Identität; Politische Identität; Deutsch; Deutschland; Germany / Intellectual life / 20th century; Germany / Ethnic relations; Aufsatzsammlung